PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Pada PT. Primatexco Indonesia, Batang) - Aditya, M. Riksa; Rahardja, Edy (Diponegoro Journal of Management, 2015)
The purpose of this researched is to know what is effect da workplace training on employee productivity by using a quantitative approach. The subject in the study were employees of PT. Primatexco Indonesia, Batang with a total of 76 persons in the unit weaving using random sampling methods. Method used to collect data in  the  research  is questionnaire. Technique  used  in  the  research  to  get  the conclusion  is  a multiple linear  regression technique using SPSS.Analysis of data using multiple linear regression analysis technique, it shown that Y = X1 + 0.361 X2 0370. It intrepret clear that training and work environment positive effect on employee productivity. Due to the significant value of the training and the work environment is less than 0.05 so, that can be concluded that there is a significant positive effect on employee productivity at PT. Primatexco Indonesia, Rod. The results of the coefficient of determination of 34.3% indicates that the ability of the independent variable (training and work environment) in explaining the dependent variable (employee productivity) while the remaining 65.7% is influenced by other variables.